Morphological and Genetic Diversity of Cucumber (Cucumis sativus L.) Fruit Development - Rebecca Grumet; Ying-Chen Lin; Stephanie Rett-Cadman; Ajaz Malik (Plants, 2022)
Cucumber (Cucumis sativus L.) fruits, which are eaten at an immature stage of development, can vary extensively in morphological features such as size, shape, waxiness, spines, warts, and flesh thickness. Different types of cucumbers that vary in these morphological traits are preferred throughout the world. Numerous studies in recent years have added greatly to our understanding of cucumber fruit development and have identified a variety of genetic factors leading to extensive diversity. Candidate genes influencing floral organ establishment, cell division and cell cycle regulation, hormone biosynthesis and response, sugar transport, trichome development, and cutin, wax, and pigment biosynthesis have all been identified as factors influencing cucumber fruit morphology. The identified genes demonstrate complex interplay between structural genes, transcription factors, and hormone signaling. Identification of genetic factors controlling these traits will facilitate breeding for desired characteristics to increase productivity, improve shipping, handling, and storage traits, and enhance consumer-desired qualities. The following review examines our current understanding of developmental and genetic factors driving diversity of cucumber fruit morphology.